2022
DOI: 10.3390/ijms23158770
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Nucleoside Transporter (NT)-Encoding Genes (SLC28 and SLC29)

Abstract: The proper regulation of nucleotide pools is essential for all types of cellular functions and depends on de novo nucleotide biosynthesis, salvage, and degradation pathways. Despite the apparent essentiality of these processes, a significant number of rare diseases associated with mutations in genes encoding various enzymes of these pathways have been already identified, and others are likely yet to come. However, knowledge on genetic alterations impacting on nucleoside and nucleobase transporters is still lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Our results suggested that in the context of MNGIE, mitochondrial and lysosomal damage coexist and reinforce each other: on the one hand, defects in mitochondrial energy metabolism increase the generation of ROS, which may in turn increase the permeability of lysosomal membranes; on the other hand, lysosomal dysfunction impedes the normal clearance of mitochondria, leading to the persistent presence of abnormal mitochondria with mtDNA defects. Similarly, defects in the ENT3 protein have been found to simultaneously lead to mitochondrial damage and lysosomal dysfunction, resulting in an accumulation of mitochondrial redundancy, increased ROS and increased lysosomal volume [ 65 , 66 ]. The mechanism behind this phenomenon may be consistent with the mechanism of mitochondrial and lysosomal nucleoside accumulation caused by TP deficiency, as studies have shown that ENT3 is localized not only in lysosomes but also in mitochondria [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that in the context of MNGIE, mitochondrial and lysosomal damage coexist and reinforce each other: on the one hand, defects in mitochondrial energy metabolism increase the generation of ROS, which may in turn increase the permeability of lysosomal membranes; on the other hand, lysosomal dysfunction impedes the normal clearance of mitochondria, leading to the persistent presence of abnormal mitochondria with mtDNA defects. Similarly, defects in the ENT3 protein have been found to simultaneously lead to mitochondrial damage and lysosomal dysfunction, resulting in an accumulation of mitochondrial redundancy, increased ROS and increased lysosomal volume [ 65 , 66 ]. The mechanism behind this phenomenon may be consistent with the mechanism of mitochondrial and lysosomal nucleoside accumulation caused by TP deficiency, as studies have shown that ENT3 is localized not only in lysosomes but also in mitochondria [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrative nucleoside transporters are transporters belonging to the solute carrier transporter family SLC29 ( Baldwin et al, 2004 ; Young et al, 2013 ; Pastor-Anglada et al, 2022 ). As their name implies, equilibrative nucleoside transporters are major players in the transport of nucleobases (adenine) and nucleosides (adenosine) through a rocker-switch mechanism ( Fig.…”
Section: Slc29a1 An Equilibrative Nucleoside Transportermentioning
confidence: 99%
“…The Augustine blood type, characterized by SLC29A1 mutations, was established as a blood group in 2015, although the antigen was first identified in 1967 ( Daniels et al, 2015 ; Daniels, 2022 ). SLC29A1-null individuals appear healthy, although pseudogout and ectopic calcification during aging have been reported ( Daniels et al, 2015 ; Pastor-Anglada et al, 2022 ). SLC29A1 deficiency has not been listed in the OMIM catalog at present.…”
Section: Slc29a1 An Equilibrative Nucleoside Transportermentioning
confidence: 99%
See 1 more Smart Citation
“…The review “Inborn Errors of Nucleoside Transporter (NT)-Encoding Genes ( SLC28 and SLC29 )” by Pastor-Anglada et al [ 1 ] summarizes the genetic alterations impacting nucleoside and nucleobase transporters, focusing on Solute Carrier ( SLC ) 29A1 , SLC29A3 , and SLC28A1 , and underlines the relationships between transporter function and pathology.…”
Section: Reviewsmentioning
confidence: 99%